Preparation, Physicochemical Properties, Biological Activity of a Multifunctional Composite Film Based on Zein/Citric Acid Loaded with Grape Seed Extract and Its Application in Solid Lipid Packaging - Ning Wang; Jiaxin Wei; Cuntang Wang; Jian Ren (Foods)
Development of bio-based active packaging systems for lipid stabilization presents critical importance in preserving lipid integrity and ensuring food safety. Zein/citric acid (Z/CA) composite films containing grape seed ethanol extract (GSEE) (0–8% w/w) were prepared by the solvent casting method. The structural, functional, and environmental properties of the films, including physical and chemical properties, mechanical properties, antioxidant capacity, antibacterial activity, oxidation inhibition effect, and biodegradability, were comprehensively characterized and evaluated. Progressive GSEE enrichment significantly enhanced film thickness (p < 0.05), hydrophobicity, and total phenolic content, while increasing water vapor permeability by 61.29%. Antioxidant capacity demonstrated radical scavenging enhancements of 83.75% (DPPH) and 89.33% (ABTS) at maximal GSEE loading compared to control films. Mechanical parameters exhibited inverse proportionality to GSEE concentration, with tensile strength and elongation at break decreasing by 28.13% and 59.43%, respectively. SEM microstructural analysis revealed concentration-dependent increases in surface asperity and cross-sectional phase heterogeneity. Antimicrobial assays demonstrated selective bacteriostatic effects against Gram-negative pathogens. Notably, the composite film containing 6 wt% GSEE had a remarkable restraining effect on the oxidation of lard. The soil degradation experiment has confirmed that the Z/CA/GSEE composite film can achieve obvious degradation within 28 days. The above results indicate that the Z/CA/GSEE composite material emerges as a promising candidate for sustainable active food packaging applications.